Effects of the Temporal Scale of Observation on the Analysis of Aquatic Invertebrate Metacommunities - Castillo-Escrivà, Andreu; Mesquita-Joanes, Francesc; Rueda, Juan (Frontiers in Ecology and Evolution, 2020)
The development of metacommunity theory has been followed by empirical tests using field data, mostly focused on the role of spatial and environmental gradients on metacommunity structures. These studies showed an important dependence of the results on the observational scale considered (i.e. spatial grain, sampling spacing and extent). However, few works deal with time per se as a component explaining these structures, even when data from periodic sampling are available. We suggest adding time explicitly in metacommunity analysis, but taking into account that the temporal observational scale used could affect the outcome of the estimated influence of environment, space and time, as previously seen for spatial scale variation. Here, we analyze both temporal and spatial scale dependence with simulated and empirical metacommunities of aquatic invertebrates. The relative importance of time was primarily dependent on the strength of spatial processes (i.e. spatially-variable selection or dispersal limitation) at all temporal scales considered, because strong spatial effects temporally desynchronized the metacommunities. However, expanding the study duration increased the temporal relevance, whereas increasing the sampling lag reduced it. Our results reveal a major role for temporal scale in the analysis of metacommunity dynamics and emphasizes the temporal perspective of metacommunities, suggesting novel and interesting avenues in this framework.